2021
DOI: 10.1186/s10194-021-01229-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dural inflammatory soup application on activation and sensitization markers in the caudal trigeminal nucleus of the rat and the modulatory effects of sumatriptan and kynurenic acid

Abstract: Background The topical inflammatory soup can model the inflammation of the dura mater causing hypersensitivity and activation of the trigeminal system, a phenomenon present in migraineurs. Calcitonin gene-related peptide, transient receptor potential vanilloid-1 receptor, and neuronal nitric oxide synthase are important in the sensitization process there. 5-HT1B/1D receptor agonists, triptans are used as a treatment of migraine. Kynurenic acid an NMDA antagonist can act on struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 80 publications
1
23
1
Order By: Relevance
“…Indeed, in our experimental model, the classical algogen capsaicin operating via calcium-permeable TRPV1 receptors, promoted the large release of CGRP. Likewise, inflammatory conditions in the meninges can induce significant CGRP release, which was blocked by kynurenic acid, suggesting involvement NMDA receptors in this effect [54]. However, we did not find here the elevation of CGRP release after glutamate or NMDA treatments.…”
Section: Discussioncontrasting
confidence: 75%
“…Indeed, in our experimental model, the classical algogen capsaicin operating via calcium-permeable TRPV1 receptors, promoted the large release of CGRP. Likewise, inflammatory conditions in the meninges can induce significant CGRP release, which was blocked by kynurenic acid, suggesting involvement NMDA receptors in this effect [54]. However, we did not find here the elevation of CGRP release after glutamate or NMDA treatments.…”
Section: Discussioncontrasting
confidence: 75%
“…Elevated levels of KYNA have also been implicated in rapid progression among lung cancer patients [ 17 ], HIV-related illnesses [ 18 ], cataracts [ 19 ], tick-borne encephalitis [ 20 ], and partial seizures in epileptic patients [ 19 ]. Most recently, KYNA has also been associated with antidepressant-like and antimigraine-like effects as well [ 21 , 22 ].…”
Section: The Kynurenine Pathwaymentioning
confidence: 99%
“…KYNA levels are increased in the blood of patients suffering from multiple sclerosis [53], inflammatory bowel disease [54], and type 2 diabetes [55], while in the blood of patients with chronic schizophrenia [56], Alzheimer dementia [57], cluster headache [58], chronic migraine [59], and Parkinson's disease [57] KYNA levels are decreased. Interestingly, the recent review pointed out that lover levels of KYNA accompany psychiatric disorders affecting cognitive domains, but higher levels of KYNA are observed in patients suffering from schizophrenia [20,[60][61][62]. In people affected by Huntington's disease, a reduction in KYNA in the cerebrospinal fluid and several brain regions was observed [60].…”
Section: Kynurenic Acidmentioning
confidence: 99%
“…In patients suffering from rheumatoid arthritis, a positive correlation between serum KYNA and morning stiffness and pain was shown [61]. Additionally, it was observed that kynurenic acid exerts analgesic properties in an animal model of migraine, induced by dural inflammatory soup [62]. Therefore, it seems possible that pharmacological intervention affecting the production of KYNA-and at the same time the processes connected with the activity of excitatory amino acids in the CNS-may contribute to pain modulation.…”
Section: Kynurenic Acidmentioning
confidence: 99%